The Marion Milner Method Psychoanalysis, Autobiography, Creativity - Halton-Hernandez, Emilia (Taylor & Francis, 2023)
This book traces the development of British psychoanalyst Marion Milner's (1900-98) autobiographical acts throughout her lifetime, proposing that Milner is a thinker to whom we can turn to explore the therapeutic potentialities of autobiographical and creative self-expression. Milner's experimentation with aesthetic, self-expressive techniques are a means to therapeutic ends, forming what Emilia Halton-Hernandez calls her "autobiographical cure." This book considers whether Milner's work champions this site for therapeutic work over that of the relationship between patient and analyst in the psychoanalytic setting. This book brings to light a theory and practice which is latent and sometimes hidden, but which is central to understanding what drives Milner's autobiographical work. It is by doing this work of elucidation and organisation that Halton-Hernandez finds Milner to be a thinker with a unique take on psychoanalysis, object relations theory, creativity, and autobiography, working at the interstices of each. Divided into two fascinating sections exploring Milner's distinctive method and the legacy and influence of her work, this book will appeal to psychoanalysts, art therapists, philosophers, and art and literary researchers alike. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.